Ectopic pregnancy an obstetric emergency: retrospective study from medical college Ambala, Haryana, India - Yadav, Shweta Tomar; Kaur, Simmanjit; Yadav, Sachin Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy remains the leading cause of maternal death in early pregnancy, the overall incidence of ectopic pregnancy is increasing but with improved diagnostic techniques and conservative management, case fatality rate has reduced. This study was undertaken to evaluate the incidence, clinical profile, associated risk factors, management and outcome of cases diagnosed as ectopic pregnancy. Methods: This retrospective study was conducted at MMIMSR Mullana, Ambala from 1st January 2014 to 31 December 2015. All women admitted with ectopic pregnancy in the gynae department were taken in the study. Results: The incidence of ectopic pregnancy in our institute was 0.97 %, mainly affecting young multiparous women, out of 36 cases 15 (41.7%) patients had risk factors previous abortion was commonest (19.4%), followed by history of infertility, tubal ligation, ectopic pregnancy, Cu T insertion. Acute abdominal pain was the commonest (94.4%) symptom 2/3 patients had tachycardia and abdominal tenderness, 10 were in shock. mild to moderate anemia present, while 17 % severely anemic, urine pregnancy test was positive in all. 5 hemodynamically stable patients given single dose intramuscular methotrexate, surgical intervention in 31 cases by either laparoscopy or laparotomy, laparoscopy in 4 patients, 1 had to be converted to laparotomy. Fallopian tubes were commonest site; Ampulla was the commonest site in tubal rupture. Conclusions: The ectopic pregnancy remains a public health issue. Timely diagnosis and transfer to higher center in hemodynamically stable state along with the use of conservative surgery or medical management can reduce morbidity and mortality.